Visual Methods of Teaching Younger Schoolchildren as A Way to Develop and Improve Learning Activities - Davidova Ekaterina Pavlovna (Peerian Journals Publishing, 2023)
Any area of subjects of an is natural-mathematical cycle cannot do without graphic preparation because our language is insufficient for concrete and simultaneously volume representations of visual perception. Necessity of expression of cognizable subjects is basic in thought process of training in the field of these subjects. Practical application of knowledge, skills on performance of graphic representations takes place not only in system of school training, but also gets high-grade sense after its termination.
Keywords: training visual teaching methods; graphic display; preparation of the future teachers